Development of interactive multimedia based on lectora inspire to improve understanding about disaster mitigation material in senior high school - Wirda Tria Rahma; Sugandi Dede (E3S Web of Conferences)
Media that gives pupils a comprehensive grasp is necessary to improve comprehension of disaster mitigation content. One of the teaching strategies that can raise the standard of geography instruction is information and communication technology-based learning. An application for creating interactive learning multimedia and e-learning content is called Based Lectora Inspire. The purpose of this study was to: (1) develop and find out the feasibility of interactive multimedia based on Lectora inspire about disaster mitigation materials as a geography learning medium (2) determine the effectiveness of the Lectora inspire media that was developed to improve the results of students understanding of the material. The four steps of the Borg and Gall model needs analysis, multimedia model design, media development, and multimedia evaluation are used in this study’s Research and Development (R&D) methodology. The study’s findings indicate that: (1) With a very good category, interactive multimedia based on Lectora inspire on disaster mitigation materials can be used as a geography learning tool; (2) Lectora-inspired interactive multimedia effectively enhances comprehension of disaster mitigation content. Compared to audio-visual media, interactive multimedia based on lectora has a greater impact on enhancing comprehension of disaster mitigation in this study.